Why women have a greater intimacy in their friendship relationships? - Ruiz-Aranda, Desiree; Zaccagnini-Sancho, José Luis (My University, 2013)
The objective of this study was to analyze gender differences in the quality of interpersonal relationships (Zaccagnini & Martin, 2008) from a Positive Psychology perspective (Berscheid, 2003). In addition, discussed the contribution of emotional regulation (Gross y John, 2003) as a predictor of these dimensions. The results of the study indicate that women have a higher quality of social relationships than men, and that this is related to the ability to regulate emotions. These findings suggest that women used to a lesser extent than men emotional suppression strategies which creates a more intimate relationship in their social relations. Our findings suggest that emotional regulation skills predict better positive interactions.
Keywords: Relaciones humanas; Emociones; Social relations; gender; Emotional regulation